2013
DOI: 10.1007/s10943-013-9803-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Portuguese Version of the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS-P) in Clinical and Non-clinical Samples

Abstract: Despite Brazil's high levels of religious involvement, there is a scarcity of validated religiousness/spirituality (R/S) measures in Portuguese, particularly multidimensional ones. This study presents the validation of the Portuguese version of the "Brief Multidimensional Measure in Religiousness and Spirituality" (BMMRS) within the Brazilian context. Inpatients (262) and caregivers (389) at two hospitals of Brazil answered the BMMRS, the DUREL-p, and a sociodemographic questionnaire. The internal and converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
3
19
0
11
Order By: Relevance
“…If we would do another study in the future, we would use standardized BMMRS‐P questionnaire for religion/spirituality (Curcio et al. ).…”
Section: Limitationsmentioning
confidence: 99%
“…If we would do another study in the future, we would use standardized BMMRS‐P questionnaire for religion/spirituality (Curcio et al. ).…”
Section: Limitationsmentioning
confidence: 99%
“…More recently, Curcio, Lucchetti and Moreira-Almeida (2015) have published a study reporting on an initial validation of a Portuguese version of the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS-P). Using both clinical and non-clinical samples, Curcio et al (2015) found evidence of adequate reliability (test-retest) and fairly good support for internal, convergent and discriminant validity of the various BMMRS-P scales. Unfortunately, the BMMRS-P is not a theory driven measure nor does it have an empirically grounded organizational structure.…”
Section: Introductionmentioning
confidence: 88%
“…It is a syncretic amalgam of 11 scales measuring various concepts that were deemed important for health research by a working group assembled by the National Institute on Aging and the Fetzer Institute in the United States (see Fetzer Institute, National Institute on Aging Working Group, 1999). As importantly, Curcio et al (2015), do not directly evaluate the extent to which the BMMRS-P is actually capturing the constructs with Brazilian respondents in a manner which shows equivalence to that seen in American samples (i.e., they do not examine structural/configural and measurement invariance in a rigorous manner). Consequently, while their findings are promising and provide support for further psychometric research on the BMMRS-P, they fall short of supplying strong evidence of cross-cultural validity and investigators using the test with Brazilians should exercise caution in how they interpret its scores with Brazilian respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Estes aspectos têm sido associados com a resultante do compromisso religioso (Curcio et al, 2016). Por fim, outro instrumento, a FACIT Sp 12 (Peterman et al, 2002), traduzida e validada por Lucchetti et al (2015), pretende avaliar harmonia, paz, senso de força, fé e significado. Apresenta, como exemplo, os itens como "Sinto-me em paz" e "Independente do que acontecer com a minha doença, tudo vai acabar bem".…”
Section: Controvérsias Na Mensuração De Espiritualidadeunclassified
“…Escala de experiências espirituais diárias, o coeficiente de alfa de Cronbach foi de 0,91 (Kimura et al, 2012), e na escala BMMRS-P, o maior índice encontrado, em um dos domínios, foi de 0,88 (Curcio et al, 2013). Na escala FACIT-Sp o coeficiente alfa variou de 0,893 para a escala total e 0,655 para a subscala de Significado (Lucchetti et al, 2015…”
Section: Atitudes/consequênciasunclassified